Sociology between the Past and the Future: Traditions and Prospects - M Petrusek (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2013)
The article by outstanding Czech sociologist Miloslav Petrusek (1936—2012) discusses a number of theoretical, methodological and practical issues of great importance for sociology today. In particular, the author touches upon various approaches to the classification of the Western sociological tradition (R. Collins, R. Boudon), raises the fundamental question of the specific nature of sociological cognition of social phenomena, characterizing its 'multi-paradigm' status, points out a number of difficulties connected with the peculiarities of teaching sociology in universities under the conditions of radical pluralization of intellectual life, typical of the 'post-modern epoch'.